Avascular Necrosis of the Foot and Ankle in a Patient with Systemic Sclerosis: A Case Based Review - H. Wastyn; M. Leys; F. Michels; A.-L. Deleu; E. Vereecke; G. Matricali; S. Clockaerts (Современная ревматология)
This review describes a case of atraumatic avascular necrosis in the foot and ankle in a patient with systemic sclerosis who did not receive corticosteroid therapy. Both avascular necrosis and systemic sclerosis are uncommon disease entities. This case demonstrates that vasculitis and secondary vasoconstriction in the pathogenesis of systemic sclerosis are important risk factors for the development of avascular necrosis of the foot and ankle. Therefore, if these patients develop chronic foot and ankle pain, avascular necrosis should be included in the differential diagnosis, even if they do not receive corticosteroids. For the diagnosis and follow-up of avascular necrosis MRI remains the gold standard. Thus, MRI should be used to diagnose avascular necrosis in an early stage. Level of Clinical Evidence: 4.